The INTEGRASI NILAI-NILAI ANTI KORUPSI DALAM PEMBELAJARAN AKHLAKUL KARIMAH DI RA AL MA'RUF - Putri Saniyah (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2026)
Abstract This study aims to describe the integration of anti-corruption values in Akhlakul Karimah learning at RA Al Ma’ruf. The research employed a descriptive qualitative method through observation, interviews, and documentation involving teachers and classroom activities. The results show that anti-corruption values such as honesty, responsibility, discipline, and cooperation are naturally integrated into learning activities through habituation, teacher modeling, and thematic learning. Teachers play a vital role in instilling moral values from an early age using joyful and contextual approaches. The implementation of these values has proven to enhance children’s moral awareness, particularly in practicing honesty and responsibility in daily life.